(3eUHGM GdCfGe aj TQM TQGjY GdESdGes - (3GdHOjQj GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3bhg cJGH GdaQGFV hGdfXQ aj GdebOeGJ hGdebGUO hGddhGMb Cbhd (B: (3GYde Cf GdCUd aj GdEQK HYO GLeGY GdeSdejf Hd GdVQhQI ef GdOjf aj GdcJGH hGdSfI Hd hQO GdMK Ydi JYdjegG hJYdegG hCfgG fUa GdYde (B...s
(3BNQgG (B:s
... (3ceG fU Ydjg ZjQ hGMO GdJUQjM Hg CjVG Hd aj ZGjI GdeQGO Cf GdeUfa aj GdaJhi Hd aj GdLhGgQ Cf dG GLO ajg NdGaG hEf CTYQ Hg fSHJg Edi GdeUfa hcja cGf aGdCUd aj Pdc bGYOI GddRhe (B.. (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3Gd`CYdGe (B2/121s
(3GdPQjYI (B21 / 68 ( 4132)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis